2012
DOI: 10.1158/0008-5472.can-11-0534
|View full text |Cite
|
Sign up to set email alerts
|

IFNβ Produced by TLR4-Activated Tumor Cells Is Involved in Improving the Antitumoral Immune Response

Abstract: Toll-like receptor (TLR) ligands may be a valuable tool to promote antitumor responses by reinforcing antitumor immunity. In addition to their expression in immune cells, functional TLRs are also expressed by many cancer cells, but their significance has been controversial. In this study, we examined the action of TLR ligands on tumor pathophysiology as a result of direct tumor cell effects. B16 murine melanoma cells were stimulated in vitro with a TLR4 ligand (LPS-B16) prior to inoculation into TLR4-deficient… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 46 publications
2
26
0
Order By: Relevance
“…In murine melanoma cells, TLR4 activation before inoculation significantly inhibits in vivo tumor growth through T cell activation (Andreani et al 2007;Nunez et al 2012). By contrast, other studies suggest that TLR activation induces tumor cell proliferation and promotes angiogenesis, invasion, and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…In murine melanoma cells, TLR4 activation before inoculation significantly inhibits in vivo tumor growth through T cell activation (Andreani et al 2007;Nunez et al 2012). By contrast, other studies suggest that TLR activation induces tumor cell proliferation and promotes angiogenesis, invasion, and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…The ligation of CD40 on the surface of tumor cells inhibits the growth of tumor and induces apoptosis [46]. Besides CD40LG, IFN-β has also been found to play critical role in anti-tumoral immune response [47]. Interestingly, Moschonas has indicated that stimulation of CD40 by its ligand has promoted the expression of IFN-β through the binding IRF7 to its promoter.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, both CD40L and IFN-b confer negative effects on carcinoma growth by improving tumor cell immunogenicity (4,14,15) and triggering direct antiproliferative and proapoptotic properties (37)(38)(39)(40)(41). Both CD40L and type I IFNs also act on immune cells to augment Th1 cell responses, enhance expression of MHC class I molecules, and generate NK and T cellmediated cytotoxicity (reviewed in Refs.…”
Section: Discussionmentioning
confidence: 99%